2000
DOI: 10.1046/j.1440-1711.2000.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential interleukin‐6 mRNA expression in Nippostrongylus brasiliensis infection of susceptible and resistant strains of mice

Abstract: SummaryIntestinal parasitic infection is still a major problem in humans and animals, yet host immunity against gut parasitic infection remains partially understood. Eosinophilia and mastocytosis are features of such infection that have been shown to be genetically controlled. The expression of IL-6 is detected in eosinophils, mast cells and neutrophils and may be responsible for the regulation of leucocytes at infective sites. The relationships between IL-6 expression, eosinophilia, mastocytosis and host immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…IL-6 and IL-8 have been reported to play an essential role in directing mechanisms which regulate inflammation (Moldawer 1994). During parasitic infections, IL-6 was postulated to play a central role in host defense mechanism by altering both inflammatory and immune responses (Bao et al 2000). Long et al (2001) have observed that culture filtrates of B. hominis significantly elevated the release of IL-8 gene expression in human colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-8 have been reported to play an essential role in directing mechanisms which regulate inflammation (Moldawer 1994). During parasitic infections, IL-6 was postulated to play a central role in host defense mechanism by altering both inflammatory and immune responses (Bao et al 2000). Long et al (2001) have observed that culture filtrates of B. hominis significantly elevated the release of IL-8 gene expression in human colonic epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We are of the opinion that the role of IL‐6 in parasitic infections is more general and important than hitherto recognized. Supporting this view are studies that show high levels of IL‐6 in T. crassiceps infections, 29,30 the increase in the number of gut cells expressing IL‐6 mRNA in sheep immunized with Trichosirongylus colubrofonizis , 31 the association between IL‐6 and host immunity in mice infected with Nippostrongylus brasiliensis , 32 S. mansoni ‐induced synthesis of IL‐6 in pulmonary microvascular endothelial cells, 33 the requirement of IL‐6 in host resistance to Trypanosoma cruzi infections, 34 and the correlation between local and systemic IL‐6 levels and inflammatory responses in experimental 35 and in human schistosomiasis 36 …”
Section: Discussionmentioning
confidence: 96%
“…IL6 is a cytokine and has both pro- and anti-inflammatory properties [ 85 87 ]. MCs of both mammals and fish have been known to produce IL6 [ 88 , 89 ]. As a modulator of the immune system [ 90 , 91 ], IL6 is rapidly upregulated in response to pathogens or to other pro-inflammatory mediators, such as IL1-β or TNF-α [ 85 , 89 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…In E. lucius , we observed that anti-IL6 immunoreactive MCs were significantly higher in number in the infected intestine, in comparison to uninfected fish. Bao et al [ 88 ] reported increased levels of IL6 mRNA in the gut of resistant mice (BALB/c) infected with the nematode Nippostrongylus brasiliensis . The high levels of IL6 mRNA were closely associated with gut eosinophilia and mastocytosis in the resistant strain of mice [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation